260 Growth Performance and Gut Integrity of Nursery Pigs Fed Diet with butyric Acid and Enzymatically Hydrolyzed Yeast Product. (7th May 2021) - Hong, Jinsu; Kim, Hee Seong; Patterson, Rob; Woyengo, Tofuko A
Abstract: The objective of this study was to evaluate the effects of butyric acid (BA) and enzymatically hydrolyzed yeast product (EYP) on growth performance and gut health of nursery pigs. A total of 96 weaned pigs (initial body weight = 6.60 kg) were housed in 24 pens (4 pigs/pen) and fed 3 diets in a randomized complete block design. The diets were corn-soybean meal-based without or with 0.05% BA or 0.1% EYP. The diets were fed in 2 phases; Phase 1: d 0 to 7 and Phase 2: d 7 to 20. Growth performance and fecal score were determined by phase. One pig from in each pen was selected for measuring organ weights, gut permeability, and electrophysiological parameters of jejunum mounted in Ussing chambers. The selected pigs were sacrificed at a rate of 6 pigs (balanced for diets) per day from d 10 to 17. Dietary BA increased (P < 0.05) gain to feed ratio for d 7 to 20 by 5.8% and for entire study period by 15.8%. Fecal scores were unaffected by dietary BA or EYP. Dietary EYP increased (P < 0.05) weight of cecum as a proportion of live body weight by 36.4%. Dietary BA decreased (P < 0.05) the flow of fluorescein isothiocyanate-dextran from mucosal to serosal side of jejunum by 31.7%, implying that dietary BA reduced jejunal permeability. Jejunal short circuit current was decreased (P < 0.05) by dietary BA or EYP. However, jejunal trans-epithelial electrical resistance was unaffected by dietary BA or EYP. In conclusion, dietary BA improved feed efficiency and reduced jejunal permeability to fluorescein isothiocyanate-dextran, implying that it can improve the gut health of weaned pigs through reduced jejunal permeability to toxins. Dietary EYP increased caecum weight, implying that it can improve hindgut fermentation in weaned pigs.